PENGARUH AROMATERAPI LAVENDER UNTUK MENGURANGI NYERI PERSALINAN: A SYSTEMATIC REVIEW - Nova Linda Rambe (Jurnal Ilmiah Kebidanan Imelda, 2022)
Pain is a state of pain and discomfort felt during labor, which can cause pain both physiologically and psychologically. This pain is caused by the contraction of the uterus and the opening of the birth canal. One way to reduce pain is to use non-pharmacological methods, namely offering lavender aromatherapy. Giving lavender aromatherapy can be done by massage and inhalation (inhaled). This study used a systematic review method with the aim of knowing the effect of giving lavender aromatherapy to reducing pain intensity in laboring mothers. This systematic review examines articles published on the Google Scientist website from 10 reviewed journals. Based on this system, it can be said that there is an effect of giving lavender aromatherapy to mothers giving birth to reduce the intensity of the pain felt.